(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Over the medieval centuries, the Paduan authorities implemented an ambitious policy of control and exploitation of the water resources of the city and the territory which has earned them the praise of Dante as well as that of numerous scholars and historians. However, an analysis of published and unpublished sources allows us to appreciate the downside, that is, a situation of hydrogeological instability in various sectors of the Paduan countryside. Congenital instability, in some cases, but in numerous other cases induced or in any case aggravated precisely by that utilitarian policy in the field of water resources which led to important interventions on the Brenta and Bacchiglione rivers, the opening of new waterways such as the Battaglia canal, the realization of embankments, reclamations etc. The lack of a comprehensive and detailed overview, the limited scientific knowledge, the scarce economic resources available have led to a situation of hydrogeological instability that, for some areas, persists until the present.